Moral responsibility in collective contexts - Isaacs, Tracy Lynn. (New York ; Oxford : Oxford University Press, 2011)
Tracy Isaacs argues that an accurate understanding of moral responsibility in collective contexts requires attention to responsibility at the individual and collective levels.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Responsibility -- Social aspects